Optimalisasi Potensi Lokal: Pelatihan Pembuatan Basreng Ikan Selengek bagi Ibu-Ibu Desa Panca Mukti - ijayani ijayani; Alfin Julianto; Sofino; Citra Dwi Palenti; Nelda Sari Siregar (Journal of Community Empowerment, 2026)
This community service activity aims to improve the knowledge, skills, and business readiness of the community through training in making basreng (shrimp cake) from selengek fish, a processed, value-added product. The target group is 20 coastal communities, particularly housewives. The activity was implemented through three stages: planning (problem identification and needs mapping), implementation (socialization, material provision, demonstrations, and practical assistance), and evaluation through observation and analysis of pre- and post-test results. The results showed improvements in participants' knowledge, processing skills, product quality, and business readiness after the training. In short, the training on making basreng from selengek fish has proven effective in increasing community capacity in processing local fishery products and has the potential to boost income and economic well-being sustainably